Organisation and ordering of 1D porphyrin polymers synthesised by on-surface Glaser coupling - Saywell, Alexander; Browning, Abigail S.; Rahe, Philipp; Anderson, Harry L.; Beton, Peter H. (Royal Society of Chemistry, 2016)
One-dimensional polymer chains consisting of π-conjugated porphyrin units are formed via Glaser coupling on a Ag(111) surface. Scanning probe microscopy reveals the covalent structure of the products and their ordering. The conformational flexibility within the chains is investigated via a comparision of room temperature and cryogenic measurements.